2010
DOI: 10.1097/bot.0b013e3181d048b8
|View full text |Cite
|
Sign up to set email alerts
|

Does the Zone of Injury in Combat-Related Type III Open Tibia Fractures Preclude the Use of Local Soft Tissue Coverage?

Abstract: There was a significantly lower amputation and reoperation rate for patients treated with rotational coverage. Contrary to our hypothesis and previous reports, the zone of injury in combat-related open tibia fractures does not preclude the use of local rotational coverage when practicable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…17,22 In the early war data, reconstructive surgeons recommended using local tissue over microvascular procedures when possible, citing higher success rates and decreased infection, reoperation, and amputations. 7,8 Despite these studies, our group has observed an increased use of free tissue transfer, from 14% in 2004 to 74% in 2011 ( p < 0.05). 26 As previously stated, free tissue can be harvested from outside the zone of in- jury, which is often plagued by microvascular injury, muscle necrosis, and infection.…”
Section: Translational Relevancementioning
confidence: 96%
See 2 more Smart Citations
“…17,22 In the early war data, reconstructive surgeons recommended using local tissue over microvascular procedures when possible, citing higher success rates and decreased infection, reoperation, and amputations. 7,8 Despite these studies, our group has observed an increased use of free tissue transfer, from 14% in 2004 to 74% in 2011 ( p < 0.05). 26 As previously stated, free tissue can be harvested from outside the zone of in- jury, which is often plagued by microvascular injury, muscle necrosis, and infection.…”
Section: Translational Relevancementioning
confidence: 96%
“…7 Similarly, Burns et al found a lower amputation and reoperation rate in patients treated with rotational coverage compared with free tissue transfer in the same type of patients. 8 However, local tissue has become less available, as explosive munitions have become the main mechanism of war-related injury, causing larger zones of injury. Often, the entirety of both lower extremities is damaged by the sequela of direct blast injury and the subsequent projectiles and pressure wave to the tissue.…”
Section: Scope and Significancementioning
confidence: 99%
See 1 more Smart Citation
“…Burns et al retrospectively compared rotational versus free flap coverage performed an average of 20 days after injury in severe open tibia fractures from combat. In their series of 67 patients, those treated with free flap coverage were more likely to have flap failure, require additional procedures, and go on to eventual amputation [29]. The largest series from the current conflict examined 75 pedicled rotational and free flaps with an average time to coverage of 21 days.…”
Section: Soft Tissue Coverage: Blast-related Amputationsmentioning
confidence: 96%
“…Rotational (pedicled fasciocutaneous and muscle) flaps have had more success and are being used more to cover the soft tissue defects in limbs 10. We noted that US military plastic surgeons were more involved in the treatment of maxillofacial trauma, so unlike UK practice, fasciocutaneous and pedicled gastrocnemius flaps were done by the orthopaedic trauma specialist, while free flaps were performed by the orthopaedic hand surgeons experienced in microvascular surgery.…”
Section: Traumamentioning
confidence: 99%